Akibat Hukum Anak yang Dilahirkan dalam Kawin Hamil - Wibowo, R. Tetuko Aryo; Luth, Thohir (Universitas Negeri Malang, 2020)
This study aimed to explore deeply about the legal consequences of children born as a result of married by accident. The method used is formative juridical with the main reference Article 53 Compilation of Islamic Law, Article 250 of the Civil Code, Article 42 of the Marriage Law, and the Al-Qur’an namely Surat Al Isra ‘verse 32. The results of the study indicate that based on Compilation of Islamic Law, Article 250 of the Civil Code, and Article 42 of the Marriage Law, the legal status of a child resulting from a married by accident is a legitimate child, so it has the descent, inheritance rights, and guardianship rights of both parents. However, based on the Qur’an and the opinion of jumhur ulama, the legal status of a child resulting from the married by accident depends on the length of birth from the time of marriage. If more than six months old, the child’s status is legitimate so that he is entitled to both parents. If it is less than six months, then the status is an illegitimate child, so that he is only entitled to his mother from the descent, guardianship rights, and inheritance rights.